The Effectiveness of Using Gamification Strategy in Enhancing the Motivation of Business Administration Students to Learn the Principles of Financial Management Course in Saudi Arabia - Felimban, Razaz Houssien (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aimed to examine the effectiveness of applying gamification strategies in enhancing the motivation of female students in the College of Business Administration while learning the course: Principles of Financial Management. The study employed the platform Kahoot! as an instructional tool to create an interactive and engaging learning environment. Adopting a quasi-experimental approach with a one-group design (pre-test/post-test), the study developed and administered a motivation scale before and after the intervention to measure changes in students’ learning motivation. The findings revealed statistically significant differences between the pre- and post-test results in favor of the latter, indicating the positive impact of gamification on improving students’ motivation and learning outcomes. Based on these results, the study recommends incorporating gamification elements into the design of finance courses, providing training for faculty on the use of interactive learning tools, and developing digital content that accommodates individual differences while fostering active participation. The study concludes that adopting innovative, gamification-based teaching methods contributes to the creation of interactive learning environments that align with the nature of academic courses and the directions of contemporary higher education.